Cellular Composition Changes and Nitrogen Uptake under Extra-Limited Nitrogen Conditions by Thermosynechococcus sp. CL-1 Carbon Biofixation - Tseng Chi-Ming; Ko Tzu-Hsing; Hsueh Hsin-Ta; Chen Hsing-Hui; Ray Dah-Tong; Shen Yun-Hwei; Chu Hsin (Journal of Chemistry)
Two types of culture systems were used (continuous and batch) which were fed using a simulated absorbent from a scrubber with carbonate/bicarbonate as the carbon source and nitrate as the nitrogen source by a thermophile strain, Thermosynechococcus sp. CL-1 (TCL-1) at 50°C. The lipid, carbohydrate, and protein cellular components which can be used as bioenergy precursors along with their content as a function of various C/N ratios are quantified. Maximum lipid productivity of about 150 mg L−1 d−1 is obtained while the CO2 uptake rate is 917 mg L−1 d−1 at a dilution rate of 0.06 h−1 when both carbon and nitrogen sources are not limited. With high range of nitrogen concentrations batch culture test, TCL-1 reveals extra-high affinity on nitrogen source under limited carbon source conditions since the affinity constant is 0.12 mM. In addition, the flow of carbon fixed during photosynthesis seems to switch from the protein synthesis pathway to forming carbohydrate rather than lipid under N-limitation and a high C/N ratio for TCL-1, resulting in a maximal carbohydrate content of 61%. Consequently, TCL-1 is an appropriate candidate to treat the wastewater of environment and produce the bioenergy precursors under extreme limited nitrogen conditions.